Hubungan Fasilitas Kerja dengan Kepuasan Kerja di Unit Rekam Medis Rumah Sakit - Nauri Anggita Temesvari; Desmayanti Br Subakti (Jurnal Kesehatan, 2020)
Job satisfaction in hospitals was needed to improve the performance to be achieved by the hospital. Job satisfaction could have an impact on whether or not happy employees do their jobs. One factor that affects job satisfaction is work facilities. Job satisfaction in the PGI Cikini Hospital medical record unit looks not good. This could be seen from the absence of employees by 15%. The problem complained by employees was the lack of work equipment provided by hospitals. The purpose of this study was to analyze the correlation between work facilities and job satisfaction at medical record unit PGI Cikini Hospital. This study used a cross-sectional study design with a total sample of all employees of the PGI Cikini Hospital Medical Record Unit with a total of 30 persons. The study was conducted from March to December 2019. The instrument used was a questionnaire. Analysis conducted descriptively to display the data of each variable and also analytically with Pearson correlation test to analyze the relationship between work facilities and job satisfaction. There was a strong, positive correlation between work facilities and job satisfaction (rxy=0,609). Work facilities and job satisfaction have a statistically significant linear relationship (p-value 0,000). There was a correlation between work facilities and job satisfaction at medical record unit PGI Cikini Hospital.